Assessing the incidence and wage effects of over-skilling in the Australian labour market - Kostas Mavromaras; Seamus McGuinness; Yin King Fok (Institute for the Study of Labor (IZA), 2007)
This paper examines the incidence and wage effects of over-skilling within the Australian labour market. It finds that approximately 30 percent of employees believed themselves to be moderately over-skilled and 11 percent believed themselves to be severely over-skilled. The incidence of skills mismatch varied little when the sample was split by education. After controlling for individual and job characteristics as well as the potential bias arising from individual unobserved heterogeneity, severely over-skilled workers suffer an average wage penalty of 13.3 percent with the penalty ranging from about 8 percent among vocationally qualified employees to over 20 percent for graduates.
urn:nbn:de:101:1-2008032740
Keywords: 330; Überqualifikation; Arbeitsmarkt; Lohn; Australien